Peran Business Tourism dalam Daya Saing Destinasi: Perspektif Mahasiswa Pariwisata - Nasution, Rahmad Kurnia Abdik; Nurlaeli, Sitti (Jurnal Ilmiah Ilmu Pariwisata, 2025)
Business tourism, particularly the Meetings, Incentives, Conferences, and Exhibitions (MICE) sector, has played a crucial role in enhancing the competitiveness of tourism destinations. This study analyzed the role of business tourism in strengthening Medan’s destination competitiveness from the perspective of students in the Tourism Study Program at Universitas Katolik Santo Thomas. A mixed-methods approach was employed, combining quantitative surveys with students and qualitative interviews with industry practitioners and academics. The findings indicated that while Medan’s MICE infrastructure is relatively adequate, it remains suboptimal for attracting large-scale international events. The destination’s promotional strategies were found to be ineffective, and stakeholder collaboration lacked cohesion. Students were identified as having significant potential to support business tourism digitalization through technology-driven marketing innovations. The ABDIK (Business Tourism Digital Activation by Students) concept was introduced as a novel approach to empower students in MICE development. The study concluded that business tourism is a strategic driver for destination competitiveness but requires stronger synergy among the government, industry, academia, and local communities to achieve sustainable growth.